2008
DOI: 10.1007/s00125-008-1147-0
|View full text |Cite
|
Sign up to set email alerts
|

Changing the glucose cut-off values that define hypoglycaemia has a major effect on reported frequencies of hypoglycaemia

Abstract: Aims/hypothesis The aim of this analysis was to quantify the relationship between the frequency of hypoglycaemia and various glucose cut-off points for the definition of hypoglycaemia, within a range of HbA 1c strata. Methods Data from two trials examining insulin glargine dose titration in 12,837 type 2 diabetic participants starting insulin therapy were combined. Curves for hypoglycaemia frequency plotted against endpoint HbA 1c level were constructed, using a range of glucose cut-off points for hypoglycaemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 11 publications
(9 reference statements)
0
49
0
2
Order By: Relevance
“…Similarly, in the international Addison's survey of the UK Addison's Disease Self-Help Group, 47% of the participants reported that they had needed emergency treatment at a hospital since their diagnosis, and of these 10% reported that they had needed emergency hospital treatment on four or more occasions (17). Thus, AC is relatively common in patients with PAI or SAI with a frequency in the same order of magnitude as severe hypoglycaemia requiring assistance in patients with diabetes mellitus (about 10 per 100 patient years) (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in the international Addison's survey of the UK Addison's Disease Self-Help Group, 47% of the participants reported that they had needed emergency treatment at a hospital since their diagnosis, and of these 10% reported that they had needed emergency hospital treatment on four or more occasions (17). Thus, AC is relatively common in patients with PAI or SAI with a frequency in the same order of magnitude as severe hypoglycaemia requiring assistance in patients with diabetes mellitus (about 10 per 100 patient years) (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…This is an important consideration as it is evident that the glucose level that is selected to define hypoglycaemia can influence estimates of the frequency of this therapeutic side effect-a choice that could have important clinical and commercial implications. To illustrate this, Swinnen et al [3] applied a range of different glucose levels defining hypoglycaemia to the blood glucose data from two large prospective trials of people with type 2 diabetes who had commenced treatment with insulin. As reported in this issue of Diabetologia, they unequivocally demonstrate how changing the glucose cut-off level can profoundly influence the estimated frequency of hypoglycaemia.…”
Section: Rationale For the American Diabetes Association Definition Omentioning
confidence: 99%
“…Although these responses may be preceded by some release of counter-regulatory hormones in non-diabetic individuals, the absence of glucagon secretion in insulin-deficient diabetes negates the clinical importance of defining hypoglycaemia on this basis. While the difference between 3.5 and 3.9 mmol/l may appear to be insignificant, Swinnen et al [3] have clearly illustrated how a small change in the cut-off level can magnify the prevalence of asymptomatic hypoglycaemia. Ironically, an arterialised venous glucose level of 3.9 mmol/l is probably equivalent to a capillary blood glucose level of 3.5 mmol/l.…”
Section: Which Blood Glucose Level Defines Clinically Meaningful Hypomentioning
confidence: 99%
“…The data reported by Swinnen et al [1] nicely document that a higher plasma glucose cut-off value increases the percentage of affected patients and increases the proportion of patients who are asymptomatic; but those are predictable findings. Their data also indicate that a higher cut-off value identifies a higher percentage of patients who suffer severe hypoglycaemia, i.e.…”
mentioning
confidence: 91%